COMPARATIVE EVALUATION OF COLPOSCOPY WITH CYTOLOGY FOR DIAGNOSIS OF BENIGN AND MALIGNANT CERVICAL LESIONS - Gaurav Agrawal; Shailendra Niranjan; Navdeep; Madhurendra Rajput (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: The cytological examination serves as a fundamental screening modality for cervical intraepithelial neoplasia, owing to its cost-effectiveness, ease of accessibility. While colposcopy is limited by cost, accessibility, invasiveness and low specificity. Colposcopy and cytology were considered as competing methods to detect cervical neoplasm. The study evaluates the accuracy of colposcopy for diagnosis of cervical cancer. Result: Total 27 cases of CIN I of which 7 (50%) were positive on colposcopy, 6 (42.86%) were benign lesions colposcopically and 1 (7.14%) was CIN II. For CIN II cytology had detected 6 cases as CIN II of which 5 (83.33%) was positive for CIN II colposcopically and only 1 (16.67%) was diagnosed as CIN I on colposcopy. For CIN III out of 3 cytology positive cases for CIN III, 2 (66.67%) were colposcopically diagnosed as CIN III. c2 test has been applied which was found statistically significant. Conclusion: The sensitivity and specificity of colposcopy was much higher as compared to cytology, specifically increasing for high grade cervical lesions.